Valor de la determinación de la proteína C reactiva como marcador pronóstico y de infección en pacientes críticos. - Seller Pérez, Gemma Luisa; Herrera-Gutiérrez, Manuel Enrique; Lebrón-Gallardo, Miguel; de Toro-Peinado, Isabel; Martín-Hita, Lina; Porras-Ballesteros, Jose Antonio (Elsevier, 2005)
Background and objective: C-reactive protein (CRP) has been considered a marker for infection and an aid for diagnosing sepsis. We analyze the relation of CRP to infection and outcome in intensive care units (ICU) patients. Patients and method: Prospective study on 77 ventilated patients. Expected short ICU stay or (suspected or confirmed) infection at admission were excluding criteria. 55 admissions after elective surgery were the controls. CRP measurement the first (CRP-1), third (CRP-3) and sixth (CRP-6) day of stay. APACHE II (Acute Physiology Score and Chronic Health Evaluation), SOFA (Sepsis-related Organ Failure Assessment), shock, respiratory or renal failure, leucocytes, platelets and albumin were registered. Follow-up until day 9 for infection and ICU discharge for outcome. Results: CRP-1 in controls was 5.3 (3.9) mg/l and cases 67.8 (77.4) (p < 0.001). Shock on admission was related to CRP-1: patients in shock had higher CRP-1 levels (118.6 [82.8] vs 62.8 [75.6]; p = 0.06). 40.25% of cases developed infection, and CRP-1 levels were higher in this patients (88.8 [93.9] vs 53.8 [60.9]; p < 0.05). ROC area under curve was 0.6 with a sensibility of 23% and a specificity of 89% for a level of CRP-1 > 100. Mortality was 23.4% in cases and 1.8% in controls. Age, shock, APACHE II and SOFA were related to mortality, but CRP-1 did not. ROC area under curve for CRP-1 as mortality predictor in all patients was 0.62 (0.76 for APACHE II and 0.77 for SOFA) but only in cases was of 0.49 (0.69 for APACHE II and 0.67 for SOFA). Conclusions: CRP level on admission is an useful marker for early infection but not for outcome in critically ill patients admited to the ICU.
https://openpolicyfinder.jisc.ac.uk/id/publication/19939
Keywords: Unidades de cuidados intensivos; Septicemia - Fisiopatología; Biomarcadores; Enfermos críticos; C-Reactive Protein / metabolism; Critical Illness / mortality; Intensive Care Units; Sepsis / physiopathology; C-Reactive Protein